Challenges in the applicability of interprofessional education in the context of primary health care (Research, Society and Development, 2021)
The study aims to identify the main challenges in the applicability of interprofessional education in the context of Primary Health Care. It is an integrative literature review with a qualitative approach, guided by the following research question “What are the main difficulties encountered in the applicability of interprofessional education in the context of Primary Health Care?”. Data collection took place between September and October in the Latin American and Caribbean Literature and Health Sciences, Databases in Nursing and Scientific Electronic Library Online databases. For the search strategy, the descriptors in Health Sciences (DECS) were used, being “Interprofessional Education”, “Primary Health Care” and “Patient Assistance Team”. After the study eligibility process, it was possible to read the 8 materials in their entirety. The NASF health professionals reveal that the graduation training process has a deficit of content and practice regarding the general role in primary care, with variations from one course to another or between universities. This reveals the need for permanent education actions and meetings in daily work. Thus, given all the challenges, the development of interprofessional and interdisciplinary education will only be consolidated by the expanded, disseminated and improved educational experience so that interactions between different areas can be perceived to see the impact of these actions on Primary Health Care.